Wpływ wewnątrzorganizacyjnych przeobrażeń dostosowujących przedsiębiorstwo do warunków globalizującej się polskiej gospodarki na jego funkcję personalną - Antczak, Zbigniew (The Influence of intra-organisational transformation in globalised Polish economy on human resources management in a company, 2005)
The author presents the unique results of research, constituting part of his thesis on the highly advanced implementation of Human Resources Management in selected two service companies in globalised Polish economy. Dependening on managerial qualifications, radical organisational change (fusion and outsourcing) may improve the HRM index or can result in personal and organisational perturbation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 211-221